Simultaneous transcatheter aortic valve implantation and femoral osteosynthesis: a case report - Yuki Mitsuta; Yukiko Okamura; Yosuke Miyamoto; Dai Tanahira (JA Clinical Reports)
Abstract Background Simultaneous cardiac and non-cardiac surgeries can be beneficial for patients, but there are still few reports on this approach. Case presentation A 90-year-old woman was diagnosed with a femoral trochanteric fracture and severe aortic stenosis. A heart team conference decided to perform transcatheter aortic valve implantation (TAVI) and femoral osteosynthesis under general anesthesia on the same day. A preoperative simulation was conducted to review the surgical procedure and confirm the arrangement of the operating table and instruments. Preoperative management was carried out with attention to the risk of myocardial ischemia caused by bleeding or pain from the fracture. Transfemoral TAVI was completed without trouble, and after the patient was moved to the traction table, osteosynthesis was started. Back-up pacing with a temporary pacemaker was activated for atrioventricular block and bradycardia. After completing the surgery, the patient recovered from anesthesia, and extubation was performed after confirming the absence of paralysis. The patient had no noticeable postoperative complications and successfully underwent rehabilitation. Conclusions Through meticulous preparation and perioperative management, we were able to perform TAVI and femoral osteosynthesis simultaneously, achieving a favorable outcome.